2010
DOI: 10.1097/acm.0b013e3181d3ca17
|View full text |Cite
|
Sign up to set email alerts
|

Are MD–PhD Programs Meeting Their Goals? An Analysis of Career Choices Made by Graduates of 24 MD–PhD Programs

Abstract: Purpose MD–PhD training programs provide an integrated approach for training physician–scientists. The goal of this study was to characterize the career path taken by MD–PhD program alumni during the past 40 years and identify trends that affect their success. Method In 2007–early 2008, 24 programs enrolling 43% of current trainees and representing half of the National Institutes of Health-funded MD–PhD training programs submitted anonymous data on 5,969 current and former trainees. Results The average pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
278
2
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(300 citation statements)
references
References 20 publications
(32 reference statements)
14
278
2
6
Order By: Relevance
“…A study of MD-PhD programs found that 81% of graduates were employed in academia and 61% had obtained research funding. 7 These data provide evidence that such dual-degree programs in medicine are largely successful in training clinician-scientists who devote themselves to an academic research career. Importantly, established biomedical sciences represented the majority of focus for the PhD portion of the combined programs.…”
Section: The Way Forwardmentioning
confidence: 89%
“…A study of MD-PhD programs found that 81% of graduates were employed in academia and 61% had obtained research funding. 7 These data provide evidence that such dual-degree programs in medicine are largely successful in training clinician-scientists who devote themselves to an academic research career. Importantly, established biomedical sciences represented the majority of focus for the PhD portion of the combined programs.…”
Section: The Way Forwardmentioning
confidence: 89%
“…Une étude rétrospective récente, publiée dans la revue de l'association américaine des écoles de méde-cine (American association of medical colleges -AAMC), s'est intéressée aux MD-PhD programs afin de savoir si ces filières atteignaient leurs objectifs [1] .…”
Section: Les Md-phd Programs Aux éTats-unis Et Dans D'autres Pays éTrunclassified
“…Fortunately, MD-PhD programs have expanded greatly in size in past decades. 5 These programs produce clinicians and surgeons who are extensively trained in cellular and molecular biology techniques. Through the promotion of these educational programs, the clinical scientist has a broader research outlook including the possibilities and sophisticated techniques that only a laboratory offers.…”
Section: The Modern Researchermentioning
confidence: 99%